The Effectiveness of Gamification Technique to Students’ English Vocabulary Acquisition for Seventh Grade Junior High School Students at SMP N 31 Medan: Penelitian - Giovani Br Lubis; Meikardo Samuel Prayuda; Fiber Yun Almanda Ginting (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the effectiveness of gamification, particularly using the Kahoot platform, in enhancing English vocabulary acquisition among seventh-grade students at SMPN 31 Medan during the 2024/2025 academic year. Vocabulary mastery plays a crucial role in supporting the four English language skills: listening, speaking, reading, and writing. However, traditional vocabulary instruction methods often fail to engage students and result in limited retention. This quasi-experimental study employed a pre-test and post-test design to compare learning outcomes between an experimental group exposed to gamified vocabulary instruction and a control group taught through conventional methods. The findings indicate a significant improvement in the vocabulary acquisition of students taught using gamification. The experimental group achieved a mean gain score of 68.22, notably higher than the control group’s 49.97. Statistical analysis using an independent samples t-test revealed a t-count of 4.41, exceeding the critical t-value of 2.00, confirming the significance of the results. Moreover, the experimental group demonstrated more consistent progress, as reflected in the lower variance of their gain scores.